VALIDITY OF ANTHROPOMETRIC STUDY OF ANATOMICAL FEATURES OF GREATER SCIATIC NOTCH FOR GENDER DETERMINATION: A DISTINCT AND VALUABLE TOOL FOR FORENSIC IDENTIFICATION - Jadoon, Omair Khan; Sumaira Javed; Salma Shazia; Humaira Imtiaz; Sara Jadoon; Sarwat Abbasi; Aftab Alam Khan; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2024)
Background: Forensic Medicine has challenging dynamics particularly in identification of gender from bones. Pelvic bone is one of them which is commonly used in gender estimation due to variety of its features. The greater sciatic notch is the best part of pelvic bone for gender determination as its location makes it resilience to trauma even for many years. The aim of this study was to validate the various features such as width, depth angles etc. of greater sciatic notch for sex determination of the deceased. Methods: This validation study was carried out in department of Forensic Medicine and Anatomy of Ayub Medical College from June 2023 to December 2023. A sample of 70 dry unidentified pelvic bones were studied by measuring the width, depth, anterior and posterior segments, anterior and posterior angles of the greater sciatic notch. Based on these measurements, the bones were then segregated as male and female bones. After initial gender identification, the standard features of the pelvic bones as per Krogman’s classification were used for final confirmation of the gender. Results: Result showed width, Anterior segment and posterior angle of greater sciatic notch greater in females while depth of notch deeper, posterior segments, anterior angle greater in males. These parameters and measurements give a unique importance for determining the gender of individual. Conclusion: Our study shows that there is a significant difference between gender on the basis of different mentioned parameters of estimation. By using these parameters of greater sciatic notch anthropometric measurements, investigators can easily conclude important milestones of identity and determine the truth.